(untitled) (Bangladesh Journal of Botany, 2021)
With its unique square-shaped culm, Chimonobambusa hirtinoda C.S. Chao & K.M. Lan is a critically endangered species, and its natural habitat is solely restricted to Doupeng Mountain in Guizhou, China. Two small-insert libraries from C. hirtinoda were constructed and sequenced. Approximately 127.83 Gb of highquality reads were generated and assembled into 9,320,997 contigs with a N50 length of 213bp, thereby producing 8,867,344 scaffolds with total length of 2.01 Gb. An estimated genome size of C. hirtinode was 2.86 Gb on the basis of k-mer frequency analysis, with the GC content of 45.40%. The repeat rate and heterozygous ratio were 74.11 and 1.48% in C. hirtinoda genome, respectively. Finally, 65,398 SSR loci were identified in the assembled contigs, including 58.66% tri-nucleotide, 27.42% di-nucleotide, 7.94% tetranucleotide, 3.67% penta-nucleotide, and 2.31% hexa-nucleotide. Results of this study are useful not only for ecological conservation of C. hirtinoda, but also for phylogenetic studies.